Relationship of Breastfeeding on Infant Development in Surakarta - sari, Ropita; Fatsena, Rizka Adela; Parwatiningsih, Sri Anggarini; Megasari, Anis Laela; Kartikasari, M. Nur Dewi; Yunita, Fresthy Astrika; Hardiningsih, Hardiningsih; Hutomo, Cahyaning Setyo (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Breast milk is the healthiest diet for newborns since it has the best immune system of any food, has a wealth of advantages, and contains the right combination and amount of nutrients to promote an infant's growth and development, especially between the ages of 0 and 6 months. This study aimed to determine the impact of breastfeeding on infant’s development in Surakarta. Subjects and Method: This was a retrospective cross-sectional study conducted at Community Health Centre in Surakarta, Central Java on March to August 2020. A total sample of 56 infants were selected for this study. The dependent variable was infant development. The independent variable was exclusive breastfeeding. The data collected by questionnaire. The data were analyzed by Chi-Square. Results: Infants who are exclusive breastfeeding have a 25.50 times chance of developing better compared to infants who are not exclusive breastfeeding, and this is statistically significant (OR= 25.50; 95% CI= 1.14 to 572.30; p <0.001). Infant with exclusive breastfeeding had a better communication and social interaction at 6 months, and better cognition, communication, and social interaction at 12 months. Conclusion: The development of infants' psychological, linguistic, fine motor, and gross motor skills can be improved by exclusive breastfeeding. Keywords: breastfeeding, development, infants. Correspondence: Ropitasari. D-3 Midwifery Study Program of Vocational School, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Phone: 082220023585. Email : ropita.uns@gmail.com